1993
DOI: 10.1128/jcm.31.4.824-830.1993
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase chain reaction using 16S rRNA gene sequences distinguishes the two biovars of Ureaplasma urealyticum

Abstract: Several fundamental phenotypic and genotypic differences have separated strains of the genital mycoplasma Ureaplasma urealyticum into two clusters or biovars. However, the lack of an easily performed and unambiguous test to discriminate between them has hampered investigation of the relationship between these biovars and disease. We determined the 16S rRNA nucleotide sequence of U. urealyticum 27, the serovar 3 standard and representative of the parvo biovar (serovars 1, 3, 6, and 14). This sequence was compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
32
2
8

Year Published

1997
1997
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(44 citation statements)
references
References 34 publications
2
32
2
8
Order By: Relevance
“…Consequently, that method classified serovars 10 and 12 into biovar 1. This result conflicts with those of most reports, in which these two serovars are usually classified as biovar 2 on the basis of their susceptibilities to manganese, protein analysis on polyacrylamide gels, Southern blot analysis with rDNA probes, PCR based on 16S rRNA gene sequence and PCR based on MB antigen gene sequence (2,3,6,9,10). Our results with five primer pairs demonstrated that there were variations in urease genes of Ureaplasma urealyticum, and the correlations between the gene variations and biovars was not definite.…”
contrasting
confidence: 84%
See 2 more Smart Citations
“…Consequently, that method classified serovars 10 and 12 into biovar 1. This result conflicts with those of most reports, in which these two serovars are usually classified as biovar 2 on the basis of their susceptibilities to manganese, protein analysis on polyacrylamide gels, Southern blot analysis with rDNA probes, PCR based on 16S rRNA gene sequence and PCR based on MB antigen gene sequence (2,3,6,9,10). Our results with five primer pairs demonstrated that there were variations in urease genes of Ureaplasma urealyticum, and the correlations between the gene variations and biovars was not definite.…”
contrasting
confidence: 84%
“…Ureaplasma urealyticum is designated for all Ureaplasma isolated from humans (6). A 14-member serotyping scheme has been widely accepted based on the detection of differences in surface antigenicity (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic analysis has allowed two biovars to be distinguished on the basis of differences in nucleotide sequences of ureaplasma genes (1,10,15,20,22,26). For example, PCRbased methods have been used to analyze the mba and 16S rRNA genes in U. urealyticum (10,20). In the present study, we examined the 16S-23S rRNA intergenic spacer regions of the 14 serovars of U. urealyticum and showed that this region can also be used for biovar identification.…”
mentioning
confidence: 78%
“…Although U. urealyticum strains are most commonly identified by serology, serotyping of ureaplasmas has been hampered because there are no commercially available antisera. Genetic analysis has allowed two biovars to be distinguished on the basis of differences in nucleotide sequences of ureaplasma genes (1,10,15,20,22,26). For example, PCRbased methods have been used to analyze the mba and 16S rRNA genes in U. urealyticum (10,20).…”
mentioning
confidence: 99%